Assessing Communication Behaviours of Hospital Pharmacists: How Well Do the Perspectives of Pharmacists, Patients, and an Independent Observer Align?. (October 2020) - Chevalier, Bernadette A. M.; Watson, Bernadette M.; Barras, Michael A.; Cottrell, William Neil
Pharmacists need effective communication skills to provide high-quality patient care. To date, little has been published about hospital pharmacists' communication behaviours, most is atheoretical, and has not studied patients and pharmacists as a dyad. We investigated how well pharmacists' and patients' perspectives of their shared conversation aligned, and how closely these perspectives matched that of an outsider (observer). We invoked communication accommodation theory using audio-recorded, semi-structured interviews, held separately with hospital patients ( n = 48) and pharmacists ( n = 12). Quantitative analyses indicated where patients, pharmacists, and observer perspectives aligned and occasions where they did not. With some exceptions, most pharmacists and patients held similar opinions about pharmacist communication behaviours. Observer–pharmacist discrepancies highlighted areas for further communication development using communication accommodation theory as a training tool.